Body shaming: beliefs and awareness among malaysian tertiary students and the role of institutional intervention - A Hamid, Huzaifah; Ghazali, Norlizawati; Kaur, Naginder; Sulaiman, Siti Sarina; Mohd Radzi, Amizura Hanadi; Abdullah Sani, Yang Salehah (Universiti Teknologi MARA, Kedah, 2025)
The shift from childhood to adulthood is characterised by significant changes in physical, mental, sexual, psychological, and social development. These difficult years may have long-term ramifications for an individual, particularly in terms of mental health. The act of ridiculing or degrading someone's looks is known as body shaming, weight shaming, or appearance-based harassment. This frequently lowers an individual’s self-esteem and body satisfaction, which ultimately leads to depression. This study aims to determine the prevalence of body shaming among undergraduates, as well as their perception on their institution’s intervention regarding body shaming occurrences. A set of questionnaires was administered to 230 participants from six faculties in a local educational institution in Malaysia. Stratified random sampling was conducted to select the sample population of the undergraduate programmes. The results revealed that the level of awareness among undergraduates on body shaming incidences in their institution is low. Participants also admitted disregarding the body shaming incident when it happened to them. It was also found that participants were unaware of the intervention method offered by their institution, yet they believe that the institution will most likely intervene in making itself a safe environment. In conclusion, the body shaming prevalence observed in the present study is high in terms of undergraduates’ beliefs on institution’s intervention commitment, but lower in terms of its prevalence awareness among undergraduates, thus drawing attention to the need for similar studies on the subject.